Niphargus carolinensis sp. nov. (Amphipoda: Niphargidae), an Endemic Species in the Northern Distribution Area of the Genus - Dieter Weber; Traian Brad (Hydrobiology, 2023)
Niphargus carolinensis sp. nov. was sampled from the Carolina Mine located in North Rhine–Westphalia, Germany. The new species is described and compared to phylogenetically related species and species identified in nearby locations. The three phylogenetic markers (i.e., COI, 28S rRNA and ITS2) studied in the examined specimens had different sequences compared to those belonging to species present in locations neighboring the Carolina Mine, i.e., in a radius of 40 km. N. carolinensis sp. nov. is a small-to-medium-sized species that is poorly setose; has a relatively short antenna I, trapezoidal gnathopod propodites, long pereopod VI, and short uropod III; and is not differentiated sexually. The new species described herein is a case of narrow endemism and adds to the diversity of the genus Niphargus in Germany. This work is a contribution to knowledge on groundwater amphipod diversity and the systematics of the genus Niphargus close to the northern border of the distribution of this genus.